The impact of grants in combination with school-based management trainings on primary education: A cluster-randomized trial in Northern Nigeria - Sophie Ochmann; Kehinde Elijah Owolabi; Folake Olatunji-David; Niyi Okunlola; Sebastian Vollmer (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2021)
Grant disbursals and school-based management interventions are expensive interventions that have recently received growing attention from policy-makers despite their mixed success at delivering improvements in educational outcomes in a cost-effective way. This paper reports results from a large-scale, cluster randomized controlled trial that evaluated two components of the Nigerian Partnership for Education Project (NIPEP) in Sokoto state, Nigeria. School-based management committees received both a training and a grant to improve access to and quality of primary school education, especially for girls. One year after implementation, the intervention had no impact on schools' infrastructure, educational attainment or learning outcome measures. Our results show the importance of understanding the context-specific constraints inhibiting the delivery and uptake of primary school education to avoid spending 100 million USD on a program with no discernable impact.Grant disbursals and school-based management interventions are expensive interventions that have recently received growing attention from policy-makers despite their mixed success at delivering improvements in educational outcomes in a cost-effective way. This paper reports results from a large-scale, cluster randomized controlled trial that evaluated two components of the Nigerian Partnership for Education Project (NIPEP) in Sokoto state, Nigeria. School-based management committees received both a training and a grant to improve access to and quality of primary school education, especially for girls. One year after implementation, the intervention had no impact on schools' infrastructure, educational attainment or learning outcome measures. Our results show the importance of understanding the context-specific constraints inhibiting the delivery and uptake of primary school education to avoid spending 100 million USD on a program with no discernable impact.
Keywords: I21; I28; H52; O15; 330; education; school-based management; student learning; impact evaluation; RCT; Nigeria; developing countries